2011
DOI: 10.1162/jocn.2011.21613
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Signal Dynamics during Preparation and Execution for Behavioral Shifting in Macaque Posterior Parietal Cortex

Abstract: Cognitive flexibility arises from our ability to shift behaviors depending on demand changes. Behavioral shifting recruits both a preparatory process for an upcoming behavior and an execution process for the actual behavior. Although neuroimaging studies have shown that several brain regions, including posterior parietal cortex (PPC) participated in each component process, it remains unresolved how such processes are implemented at the single-cell level or even whether these processes are distinctively carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
(110 reference statements)
3
17
0
Order By: Relevance
“…Our findings also add to the neurobiological basis of the shift dimension by showing significant relationships bilaterally between the shift dimension and the superior and posterior corona radiate diffusion tensor imaging measures. This finding corroborates data where authors found activation of the posterior parietal cortex of primates during set-shifting 35 .…”
Section: Discussionsupporting
confidence: 93%
“…Our findings also add to the neurobiological basis of the shift dimension by showing significant relationships bilaterally between the shift dimension and the superior and posterior corona radiate diffusion tensor imaging measures. This finding corroborates data where authors found activation of the posterior parietal cortex of primates during set-shifting 35 .…”
Section: Discussionsupporting
confidence: 93%
“…Other work on the neural mechanisms of executive control has shown that neurons participating in rule-dependent computations are found both within posterior parietal cortex (Stoet and Snyder, 2004; Asari et al, 2005; Kamigaki et al, 2009, 2011) and prefrontal cortex (Wallis et al, 2001; Nakahara et al, 2002; Mansouri et al, 2006; Muhammad et al, 2006). A recent study of particular relevance characterized the neural mechanisms of executive control in prefrontal cortex specifically as it applied to object categorization (Roy et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of single neurons was recorded extracellularly from the posterior bank of the inferior arcuate region (Petrides, Cadoret, & Mackey, 2005;Romo, Hernández, & Zainos, 2004;Kurata & Hoffman, 1994;Kurata & Tanji, 1986;Figure 2;ipsilateral [left] hemispheres in Monkeys I and Y and both contralateral and ipsilateral hemispheres [left and right] in Monkey M) using a glass-coated tungsten or elgiloy microelectrode (Kamigaki et al, 2009(Kamigaki et al, , 2011; ∼1 MΩ at 1 kHz). The microelectrode was advanced through the intact dura mater into the cortex along a stainless steel guide tube using a hydraulic micromanipulator (MO-95C, Narishige, Tokyo).…”
Section: Recording Proceduresmentioning
confidence: 99%